Pola Pemahaman Diri dan Kepribadian Kepala Sekolah dalam Meningkatkan Kedisiplinan Guru - Akbar Tanjung; Khoirul Saleh Harahap; Ali Sanusi Rambe; Neliwati Neliwati (Journal Of Administration and Educational Management (ALIGNMENT), 2024)
This research aims to determine the pattern of self-understanding and personality of school principals in improving teacher discipline at MTsN 2 Padang Lawas. This research uses qualitative research methodology combined with descriptive techniques. Research data collection techniques include documentation, interviews, and observation. Based on the findings and results of the discussion, it was concluded that the pattern of self-understanding and personality of the principal in improving teacher discipline at MTsN 2 Padang Lawas is still not being implemented optimally as expected, for this reason, it needs to be evaluated so that it is better, because there are still weaknesses in terms of example, ability to embrace school community, lack of enforcement of discipline, and the leadership style used still needs to be improved according to competence as a leader. The obstacle for school principals in improving teacher discipline is the need for more communication and cooperation with fellow teachers. Causing increased discipline in schools to be very ineffective in its implementation. In conclusion, the personality pattern and self-understanding of the principal in improving teacher discipline at MTsN 2 Padang Lawas is still not implemented as it should be Keywords: Patterns of Self-Understanding, Principal, Teacher Discipline